Impedance-Controlled Knee Orthosis: Transitional Movements and their Effect on Knee Kinematics and Muscular Activity - Scheidl, Marc-Anton; Braun, Hannah; Akarsu, Ismail Berkay; Castellini, Claudio (IEEE International Conference on Rehabilitation Robotics, 2025)
This study investigated the effects of an impedance-controlled active knee orthosis on knee kinematics and muscle activation during transitional movements, focusing on Sit-To-Stand and Step-Up tasks. A custom hardware and software setup employed an EMG-driven impedance controller to modulate joint stiffness real-time. Four healthy participants performed Sit-To-Stand and Step-Up tasks under assisted and non-assisted conditions. The results indicated that the orthosis reduced muscle activity in stable, bilateral tasks like Sit-To-Stand, leading to lower average EMG amplitudes in the assisted leg. In contrast, for more unstable, unilateral tasks such as StepUp, changes in velocity and muscle activity were more variable. Inter-participant differences in body mass and movement strategy influenced outcomes, and the device's interference with normal muscle patterns highlighted the need for improved sensor attachment and personalized parameter tuning. These findings underscore that while EMG-based impedance control can lessen physical effort under certain conditions, its benefits depend on the task's nature and individual user characteristics. Future work should refine hardware stability, improve data quality, and explore adaptive algorithms for personalized assistance.
CRIS-Team Scopus Importer:2025-08-01